Manganese oxide nanosheets and a 2D hybrid of graphene–manganese oxide nanosheets synthesized by liquid-phase exfoliation. (6th May 2015) - Coelho, João; Mendoza-Sánchez, Beatriz; Pettersson, Henrik; Pokle, Anuj; McGuire, Eva K; Long, Edmund; McKeon, Lorcan; Bell, Alan P; Nicolosi, Valeria
Abstract: Manganese oxide nanosheets were synthesized using liquid-phase exfoliation that achieved suspensions in isopropanol (IPA) with concentrations of up to 0.45 mg ml −1 . A study of solubility parameters showed that the exfoliation was optimum in N, N-dimethylformamide followed by IPA and diethylene glycol. IPA was the solvent of choice due to its environmentally friendly nature and ease of use for further processing. For the first time, a hybrid of graphene and manganese oxide nanosheets was synthesized using a single-step co-exfoliation process. The two-dimensional (2D) hybrid was synthesized in IPA suspensions with concentrations of up to 0.5 mg ml −1 and demonstrated stability against re-aggregation for up to six months. The co-exfoliation was found to be a energetically favorable process in which both solutes, graphene and manganese oxide nanosheets, exfoliate with an improved yield as compared to the single-solute exfoliation procedure. This work demonstrates the remarkable versatility of liquid-phase exfoliation with respect to the synthesis of hybrids with tailored properties, and it provides proof-of-concept ground work for further future investigation and exploitation of hybrids made of two or more 2D nanomaterials that have key complementary properties for various technological applications.